An opposing view to United States liver allocation problems with broader sharing. Issue 2 (April 2020) - Goldberg, David
Abstract : Purpose of review: Since 2014, the liver transplant community has been debating the pros and cons of broader sharing. Over the last 6 years, lung and heart transplantation have moved to broader sharing based on 'zones' or circles around a donor hospital, with the Organ Procurement and Transplantation Network (OPTN) approving a broader kidney sharing proposal in December of 2019 (set to be implemented in December 2020). Recent findings: In 2017, the OPTN Board of Directors approved a broader sharing policy in liver transplantation that was rooted in expanding the first-line of liver sharing beyond the donor service area (DSA). Faced with the threat of litigation, this proposal was replaced with a circle-based sharing policy titled 'Acuity Circles'. After a long legal challenge, the implementation of this new policy was delayed from April 2019 until February 2020. Summary: In this review, concerns related to broader sharing in liver allocation will be addressed, in terms of the basis for broader sharing and the potential implications to liver transplantation, rooted in the Final Rule and concerns around variability in organ donation rates and access to the waiting list.